Intervensi Terapi Relaksasi Otot Progresif Untuk Menurunkan Kecemasan Pada Lansia - Ema Anindita Berliyanti; Shanti Wardaningsih (Universitas Katolik Widya Karya Malang, 2023)
Background- Elderly is a transitional period in which a person experiences a decrease in the body's abilities physically and psychologically. One of changes that occurred significantly was the psychological condition of anxiety. Progressive muscle relaxation therapy can prevent anxiety by regulating the parasympathetic nervous system and the hypothalamus to increase positive attitudes so that stressor activation in the hypothalamus is minimized. Purpose: This case study aims to determine the effectiveness of progressive muscle relaxation therapy in reducing anxiety in the elderly. Method: This study used a method in the form of a case study on one patient. Previously, the patient's anxiety level was measured using the Hamilton Anxiety Rating Scale questionnaire and then given progressive muscle relaxation therapy intervention for 7 days on a regular basis and then observed on the 4th and 7th day to assess the effectiveness of the intervention. Results: The results of the study showed that after therapy, the anxiety level of the elderly decreased from moderate anxiety (score 24) to mild anxiety (score 16) within 7 days of the intervention. Conclusion: There is an effect of progressive muscle relaxation therapy on the level of anxiety in elderly.